BUSINESS PLAN OF @NABILAGARDENA INSTAGRAM - Gardena, Nabila; Iskandar, Budi Permadi (Journal of Business and Management, 2017)
Abstract. People nowadays are familiar with the famous photo-sharing platform called Instagram. Known for its function to share your daily journey in form of photos, Instagram also become famous to create a person’s own branding and if someone’s lucky he can become another person’s inluencer and inspiration. Not to mention, one of emerging Instagram influencer, @nabilagardena, is currently expanding itself to another next level. With the purpose of inspiring and creating positivity in society, @nabilagardena will firstly aim to reach 1 million followers and increase on profit in a one-year time frame. Some programs and activities will be run to stimulate the growth of Instagram followers. The programs also strive to broaden @nabilagardena connection for keep on going and inspire a lot of people. The list of programs, which planned specifically already are brand-influencer collaboration, local and international travelling, beauty workshop, product giveaway, follower shout-out, and TV exposure. With the help of some stakeholders, the programs were already crafted each month and estimated to gain 655,610 followers to achieve the one million followers target. This business plan will use Rp150.000.000 as the initial capital from @nabilagardena year 2016 profit. After sort of calculation, @nabilagardena will have Rp754.800.000 of Gross Profit and Rp275.100.000 as the Total Expense. By the end of December 2017, @nabilagardena will get Rp479.700.000 as her Net Profit.With a strong willingness and @nabilagardena passion, this business plan will surely succeed and bring good deeds not only to the followers but also other people. Keywords: Business plan, Instagram, Social influencer, Personal income, Personal branding